2018
DOI: 10.1016/j.neuron.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Alternative 3′ UTRs Modify the Localization, Regulatory Potential, Stability, and Plasticity of mRNAs in Neuronal Compartments

Abstract: Neurons localize mRNAs near synapses where their translation can be regulated by synaptic demand and activity. Differences in the 3' UTRs of mRNAs can change their localization, stability, and translational regulation. Using 3' end RNA sequencing of microdissected rat brain slices, we discovered a huge diversity in mRNA 3' UTRs, with many transcripts showing enrichment for a particular 3' UTR isoform in either somata or the neuropil. The 3' UTR isoforms of localized transcripts are significantly longer than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
355
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(383 citation statements)
references
References 74 publications
(70 reference statements)
28
355
0
Order By: Relevance
“…We then asked what other transcript features were associated with FMRP localization targets. We observed that FMRP localization targets had much longer open reading frames and 3′ UTRs than expected (Fig 2F), consistent with previous reports that 3′ UTR extensions and alternative 3′ UTRs can regulate RNA localization in neurons (Taliaferro et al, 2016a;Tushev et al, 2018). We observed no relationship between the overall abundance of a transcript and whether or not it was an FMRP localization target.…”
Section: Fmrp Localization Targets Have Significant Enrichments Of G-supporting
confidence: 92%
“…We then asked what other transcript features were associated with FMRP localization targets. We observed that FMRP localization targets had much longer open reading frames and 3′ UTRs than expected (Fig 2F), consistent with previous reports that 3′ UTR extensions and alternative 3′ UTRs can regulate RNA localization in neurons (Taliaferro et al, 2016a;Tushev et al, 2018). We observed no relationship between the overall abundance of a transcript and whether or not it was an FMRP localization target.…”
Section: Fmrp Localization Targets Have Significant Enrichments Of G-supporting
confidence: 92%
“…This phenomenon has been under positive evolutionary pressure, as the median length and diversity of 3′UTRs increases in higher organisms (Derti et al, 2012). Importantly, 3′UTR complexity is especially relevant in neurons, as they are the cell type expressing the longest and most varied 3′ ends (Hilgers et al, 2011; Ji et al, 2009; Miura et al, 2013; Andreassi et al, 2017; Tushev et al, 2018). These observations support the notion that 3′UTR frequently harbors regulatory elements necessary for most, if not all, aspects of mRNA metabolism, from stability and subcellular localization to translation and degradation (Andreassi and Riccio, 2009; Miura et al, 2014).…”
Section: Mrna Isoformsmentioning
confidence: 99%
“…Alternative polyadenylation plays an essential role in dendritic and axonal localization of many transcripts (Shigeoka et al, 2016; Taliaferro et al, 2016; Andreassi et al, 2017; Tushev et al, 2018), including BDNF (An et al, 2008; Will et al, 2013; Vicario et al, 2015), Impa1 (Andreassi et al, 2010, 2017), importin β1 (Perry et al, 2012), mTOR (Terenzio et al, 2018), and Shank (Bockers et al, 2004; Epstein et al, 2014). Localization signals present in isoforms within the 3′UTR usually mediate the transport and activate local translation in response to extrinsic stimuli, such as neurotrophins, synaptic activation and during regeneration after injury.…”
Section: Mrna Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, nearly 2000 actively translating mRNAs were identified within the axon through an axonspecific translating ribosome affinity purification (TRAP) approach (24,25). Similarly, identification of translating polyribosomes and over 2500 distinct mRNA transcripts through deep-sequencing within the hippocampal neuropil (26,27) further suggests that neurons have a dependency on the local translation of mRNAs in distal neurite compartments (23,28).…”
Section: Introductionmentioning
confidence: 99%